Implementasi Raspberry Pi Untuk Mendiagnosis Penyakit Diabetes Melitus Melalui Warna Lidah Menggunakan Metode Otsu's Tresholding - Tri Putra Anggara; Rizal Maulana; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Misdiagnosis is the cause of treatment and maintenance of the disease to be inappropriate, perhaps even cause of death. Some technological applications are able to overcome misdiagnosis. In general, diagnosis uses technology used images as data to be processed. One disease that can be diagnosed is diabetes mellitus. In this research tongue images used to diagnose diabetes mellitus. The color of the tongue image is a parameter used to diagnose diabetes mellitus. Tongue image obtained from webcam by Raspberry Pi with the Otsu's Thresholding method. The tongue image before processing uses Otsu's Thresholding, image must be converted into grayscale, then Improves the histogram using the Histogram Equalization method. Based on the test results, the company can acquire images, become Grayscale imagery, generalize histograms by histogram equalization method and be able to diagnose diabetes mellitus through tongue color. The result of testing the acquisition image result was obtained on 100 %, testing the system the diagnosis of diseases diabetes mellitus against patients diabetes mellitus obtained accuracy 80 % and testing the system the diagnosis of diseases diabetes mellitus against patients non diabetics mellitus obtained much as 90 % accuracy. The average of the past computing time towards the tongue diabetics mellitus 0.3 seconds and computing the average of the past time towards the tongue non diabetics mellitus 0.4 seconds.